Scalp haircuts, keloids and blood-borne virus transmission risk in South Africa—The SHAKA study - Nonhlanhla Khumalo; Avumile Mankahla; Stephen Korsman; Freedom Gumedze; Wisdom Basera; Anthia Ndyenga; Lwazi Mhlanti; Mashiko Setshedi; Ruanne Barnabas; C. Wendy Spearman; Mark W. Sonderup (PLoS ONE, 2025)
Background The most frequent transmission modes of blood-borne infections (BBI), including HIV, hepatitis B virus (HBV) and C (HCV), are well documented. South Africa, an HIV epicentre, with HBV endemicity and an additional HCV burden, raises the possibility of novel transmission means. A unique style of close shave haircut that can elicit folliculitis keloidalis nuchea (FKN), may produce bleeding during haircuts and possible BBI transmission. We designed a prospective case control study to evaluate the potential risk of BBI transmission. Methods Men with FKN and non-FKN controls were recruited from 2 centres in South Africa, Cape Town and Mthatha. The presence of FKN was diagnosed by a dermatologist and clinical photographs independently corroborated by 3 other dermatologists not involved in the study. A comprehensive confidential questionnaire was administered to each participant interrogating risk factors for potential HIV, HBV, and HCV infection. Each participant was screened for HIV 1/2 (Alere Determine), HBsAg (Alere Determine) and HCV antibody (SD Bioline) using point of care tests. Positive HIV screens were confirmed with a second test, Vikia HIV 1/2 test (bioMerieux). Logistic regression analysis adjusting for the relevant confounder was used to assess the associations. Results A total of 1163 men, median age 33.4 years [IQR 27.8–42.0], were evaluated. Those who screened positive for any viral infections were significantly older than those who did not, 37.1 [IQR 31.0–44.4) vs. 32.3 [IQR 26.9–41.0] years, p < 0.001, respectively. Overall, the seroprevalence of HIV, HBV, and HCV, was 17.2%, 6.9% and 0.4%, respectively. There was no significant difference in seroprevalence for these potential BBIs between those with FKN and without, p = 0.33, 0.66 and 0.29, respectively. For HIV co-infection with HBV and HCV, findings were similar, p = 0.64 and 0.51, respectively. When controlled for whether participants knowingly bleed during haircuts, HIV seropositivity was significantly more likely in those who regularly bleed, OR = 2.51 [95% CI 1.16–5.42], p = 0.02. Other transmission risk factors for HIV, were also significantly more likely – reported sexually transmitted genital lesions or discharge, aOR = 1.58 [95% CI 1.13–2.22], p = 0.01; and a tattoo/piercing informally done, aOR = 1.84, [95% CI 1.13–2.22], p = 0.01. Similarly, although overall HCV seroprevalence was low, those HIV/HCV co-infection was more likely in those who usually bleed with a haircut, aOR = 2.43; [95% CI 1.13–5.25]; p = 0.02, those with a sexually transmitted genital lesion or discharge, aOR = 1.58 [95% CI 1.13–2.21]; p = 0.01 and those with a tattoo/piercing informally done, aOR = 1.85 [95% CI 1.27–2.72]; p < 0.01. This was not so for HBV mono-infection, p = 0.89. Overall rates of known and recorded HBV vaccination in childhood were low, however in those with no viral infection, the rate of known vaccination was higher, 25.0% vs. 16.2%; p = 0.01 respectively. Conclusion Haircut related bleeding but not FKN was associated with a higher prevalence of HIV and HIV/HCV co-infection. HBV risk was not increased and related to either vaccination and/or dominant early childhood acquisition risk of HBV in sub-Saharan Africa. HIV and HBV prevalence remains concerningly high. Risk reduction through public education is key to prevention.